2007
DOI: 10.1080/17470210600943419
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory, Strategy Execution, and Strategy Selection in Mental Arithmetic

Abstract: A total of 72 participants estimated products of complex multiplications of two-digit operands (e.g., 63 × 78), using two strategies that differed in complexity. The simple strategy involved rounding both operands down to the closest decades (e.g., 60 × 70), whereas the complex strategy required rounding both operands up to the closest decades (e.g., 70 × 80). Participants accomplished this estimation task in two conditions: a no-load condition and a working-memory load condition in which executive components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 68 publications
3
36
1
Order By: Relevance
“…Both speed and accuracy results are also in agreement with an earlier study on computational estimation (Imbo et al, 2007), in which higher load effects on the rounding-up strategy than on the rounding-down strategy were observed. Indeed,…”
Section: Latenciessupporting
confidence: 81%
“…Both speed and accuracy results are also in agreement with an earlier study on computational estimation (Imbo et al, 2007), in which higher load effects on the rounding-up strategy than on the rounding-down strategy were observed. Indeed,…”
Section: Latenciessupporting
confidence: 81%
“…Although strategy may be both cause and effect, some previous research seems to be more in accord with a strategy-as-effect hypothesis (for a brief review, see Dunlosky & Kane, 2007). For instance, Imbo, Duverne, and Lemaire (2007) investigated the role of WMC in solving arithmetic problems, and they concluded that "when fewer working memory resources were left, participants chose the simple strategy more often, especially to solve the most demanding problems" (p. 1258). Even if enhanced WMC increases the likelihood of strategy use (as per the strategy-as-effect hypothesis), it would not necessarily rule out the strategy affordance hypothesis for explaining span-cognition relationships.…”
Section: Strategy Use As a Mediatormentioning
confidence: 99%
“…The present study is especially important because we show significant lower adaptivity levels under stressful situations (i.e. working-memory load conditions; see also Imbo, Duverne, & Lemaire, 2007), albeit for one culture only.…”
Section: The Relevance Of Being Adaptivementioning
confidence: 99%